Aktualni problemi regionalizma - Kuhelj, Alenka (Teorija in praksa, 1996)
A successful development of local government requires political and economic decentralization and regionalization. What is important is not so much the legal framework as such, but its realization in actual political practice. EU has established, in order to lessen economic differences between regions of the member states, ERDF. The resources of ERDF have been allocated to the member states and not to the regions directly. Based on the European Charter on Regionalization, EU established the "European Regions". We can observe two different paths of development of local government in Europe- Western European countries tend to enlarge local units, while Eastern European countries tend to fragment them. The fragmentation of local units prevents a fuller development of local autonomy, which would include also a capacity to decide about such issues as local finances, social and welfare policy, etc. An establishment of the two tier system of local government, with regions as a second tier of local government, would open a possibility for such development.
Keywords: regionalizem; decentralizacija; regionalno gospodarstvo; local government; lokalna samouprava